Effect of Soaking Time’s Variation of Red Onion (Allium Cepa L) Extracts on Formalin Content in Mackerel Tuna (Euthynnus Affinis) - Lestyaninrum, Indah Denissa; Dhanti, Kurnia Ritma; Sulistiyowati, Retno; Kurniawan, Kurniawan (Poltekkes Kemenkes Mataram, 2023)
Mackerel tuna (Euthynnus affinis) is one of the most popular foods in the community since it is affordable and has complete nutritional content. It is a frozen fish food product so the storage period of which is relatively short. In addition, it is possible to add formalin on which. Formalin is a substance that is prohibited from being used due to its dangerous effects. The content of saponin compounds found in red onions (Allium cepa L) can be used to reduce formalin levels. This study aimed to determine the effect of variations in the soaking time of red onion extract on the formalin level in mackerel tuna and the optimal soaking time for reducing formalin levels. This study used an experimental method with a posttest control group design. The treatment was given by soaking red onion extract at a concentration of 10% in mackerel tuna containing formalin with variations in soaking time of 1 hour, 2 hours, and 3 hours which were tested quantitatively using a UV-Vis spectrophotometer. Then, the data were analyzed using a one-way ANOVA statistical parametric test and a post hoc test using Duncan's test (DMRT). The decrease of the formalin levels by soaking the onion extract for 1 hour, 2 hours, and 3 hours was 10.61%, 41%, and 73%, respectively. The result showed that there was an effect of the soaking time of red onion extract on formalin levels (p-value 0.05), and the optimal time of soaking onion extract to reduce the formalin content of the samples was 3 hours.